FRI0642 Septic arthritis screening with a fast diagnostic tool using mid infrared spectroscopy: a multi-centric study. (12th June 2018) - Albert, J.-D.; Le Corvec, M.; Martin, A.; Guennoc, X.; David, C.; Hoang, S.; Guedes, C.; Ferreyra, M.; Hoppe, E.; Legoff, B.; Jousse-Joulin, S.; Tariel, H.; et al.
Abstract : Background: Septic arthritis diagnostic is an emergency which implies a treatment with antibiotics and hospitalization. The diagnosis is based on the cytobacteriological examination of the synovial fluid (SF), but direct bacteriological examination is insensitive and the result of the culture is obtained only after several days. Therefore, there is still a need for a rapid, simple and reliable method for the positive diagnosis of septic arthritis. Such method must allow avoiding both unrecognized septic arthritis leading to major functional consequences, and overdiagnosis that will induce unnecessary expensive hospitalization and unjustified treatment with consequences in term of health and social costs. Mid-infrared (MIR) spectroscopy, that gives a metabolic profiling of biological samples, has been proposed for early and fast diagnosis. Objectives: The objective of this study was to confirm (1) the interest of mid-infrared (MIR) spectroscopy to discriminate synovial fluid samples from patients with septic arthritis from other causes of joint effusion. Methods: Synovial fluids from patients referred for suspected arthropathies were prospectively collected in six hospitals in western France and stored at -80°C. The infrared absorption spectrum was acquired for each of the frozen samples using a chalcogenide fibre sensor. The most informative spectral variables (allowing to discriminate between septic arthritis and non-septic arthritis with reference to cytobiological examination) were selected and then used to develop an algorithm. Non-frozen synovial fluids were also analysed at Rennes University Hospital, the pilot centre, to validate the algorithm. Results: The cohort consists of synovial fluid samples from patients exhibiting various etiologies. These samples (n=402), by using SF bacteriological analysis and culture and 16S PCR analysis were classified as septic arthritis (n=30) or non septic arthritis (n=372). On the frozen samples the performances of the algorithm show a sensitivity of 97%, a specificity of 71%, a VPN of 99% and a VPP of 21%, the area under the ROC curve (AUROC) was 0.91. Conclusions: This study confirms the interest of optical fibre infrared spectroscopy for the discrimination between septic and non septic synovial fluids. The high negative predictive value and the very short time (about ten minutes) required to obtain the result makes it possible to quickly rule out an infection diagnosis, which could make it possible to avoid unnecessary hospitalization and antibiotic therapy. Reference: 1. Albert J-D, et al. Joint Bone Spine2016;83:318–323. Disclosure of Interest: J.-D. ALBERT: None declared, M. Le Corvec Employee of: DIAFIR, A. MARTIN: None declared, X. GUENNOC: None declared, C. DAVID: None declared, S. HOANG: None declared, C. GUEDES: None declared, M. FERREYRA: None declared, E. HOPPE: None declared, B. LEGOFF: None declared, S. JOUSSE-JOULIN: None declared, H. TARIEL Shareholder of: DIAFIR, O. SIRE Consultant for: DIAFIR, A. JOLIVET-GOUGEON: None declared, P. GUGGENBUHL: None declared, O. LOREAL Shareholder of: DIAFIR